MAGMA-MICK: A state-of-the-art digital platform facilitating the programmatic implementation of whole genome sequencing for TB care and prevention - Prof Annelies Van Rie; Fulvio Vigilante; Dr. Walter Sanseverino; Prof Annelies Van Rie (International Journal of Infectious Diseases)
Introduction: Next generation sequencing (NGS) holds the potential to improve the clinical management and surveillance of drug-resistant pathogens, including drug resistant tuberculosis (DR-TB). Implementation of NGS into routine TB care requires technologies that communicate WGS data in a transparent, interpretable and actionable way. Furthermore, communication should be secure, adhere to privacy laws, and be integrated into existing hierarchies of the healthcare system. Methods: We MICK, a state-of-the-art secure digital platform, for the use of NGS to guide the care and prevention of (DR)-TB. The MAGMA-MICK digital platform aims to synthesize complex NGS data into easy-to-interpret visualizations and reports. To develop the platform, international and South African guidelines for treatment of drug resistant TB were reviewed. The structure of the MAGMA-MICK platform was determined using a participatory design approach, involving stakeholders across the healthcare and public health hierarchy. Stakeholder consultations were held in South Africa between 1 Nov 2023 and 30 April 2024 with pathologists at regional and national tuberculosis reference laboratories, doctors and nurses caring for patients suffering from DR-TB, health care workers involved in DR-TB prevention activities and members of the provincial and national clinical advisory committee for DR-TB. Results: Stakeholder consultations and review of guidelines identified three key issues. First, given the recent introduction of NGS, drug resistance profiles generated by NGS bioinformatics pipeline need to be certified by a pathologist before communication to a care provider. Second, a triage system is needed to ensure that treatment for children, pregnant women, patients suffering from severe extrapulmonary TB and patients infected with a strain resistant to bedaquiline, linezolid or pretomanid/delamamid is reviewed by a clinical advisory committee so that patients with hard-to-treat DR-TB receive an informed treatment recommendation from physicians experienced in managing such patients. Third, communication of the recommended regimen has to be through a safe and user-friendly system where data is presented in a clear and succinct manner. Discussion: MAGMA-MICK represents the first digital platform aimed at facilitating the use of NGS for routine care and prevention of DR-TB. Developed for the South Africa setting, the system and can be adapted to other healthcare settings for the programmatic implementation of WGS for TB care and prevention worldwide. Conclusion: The MAGMA-MICK digital platform generates trust by the health care worker in the genomic drug resistance profile and allows them to take action so that each patient receives the optimal regimen considering a combination of their clinical characteristics and the genomic drug resistance profile of the Mtb strain. Implementation research in diverse global settings is needed to build trust and ensure universal compatibility of the platform.